Conformity and Distinctiveness in a Global Institutional Framework: The Legitimation of Ontario Fine Wine - Voronov, Maxim; De Clercq, Dirk; Hinings, C. R. (Journal of Management Studies, 2013)
Abstract The study investigates how local actors pursue two paradoxical aspects of legitimacy in a global institutional framework: the need for global conformity and the need for local distinctiveness. Drawing on the notion of glocalization, it explicates how this pursuit is accomplished by actors' selective fidelity to global norms and adaptation of these norms to local conditions. The empirical work consists of a five‐year qualitative case study of the Ontario wine industry. It provides empirical evidence for the presence of several non‐mutually exclusive paths through which local actors seek legitimation in a global context. The study offers important implications for future research on legitimation and globalization.